MONITORING OF GENETIC FEATURES OF SOILS IN RIVNEN REGION - Furman, Volodymyr; Lіusak Anna; Solodka, Tetiana; Oliіnyk Vasyl (Вісник Національного університету водного господарства та природокористування. Серія «Сільськогосподарські науки», 2020)
In the article the expounded results of inspection of soils of the Rivne area are with the aim of establishing a connection of factors and terms of soil formation, distribution of soils and their properties with regional geomorphological districts, and also change of soils in the modern terms of their use for realization of monitoring of genetic features of soils. At folding the ground map of area got spatial images a 51 abolition. At generalization of variety of the ground abolitions it is now possible to distinguish seven basic their types of Research showed close enough connection to determination of factors and terms soil formation and properties of soils with geomorphological districts. Orography of locality, relief, structure of profile, depth of bedding of waterproof horizons and lithologic layers with that the constrained distribution of limous faction of grain-size distribution and together and properties of soils, influences on properties of soils. Absence of crop rotations, insufficient bringing of organic fertilizers, application of heavy technique, results in the dramatic changes of properties of soils especially water-physical. A closeness, hardness, specific surface, moisture-capacity, permeability to water, changes, potential of moisture without the improvement of that it is impossible to promote the productivity of soils, to provide the optimal water mode during a vegetation period, that in recent year is unevenly enough distributed both spatially and in time, that it is related to the change of climate.